Tecnologia educativa para o correto posicionamento em raquianestesia: ensaio clínico controlado e randomizado - Pinto, Sarah Lima (2018)
The objective was the development of a serial album for health education of the correct positioning for spinal anesthesia in cesarean section. In this sense, a multi-method research was carried out, the first phase being a methodological study and the second, a double-blind randomized controlled trial (CRCT). The construction of the serial album contemplated the stages: elaboration of the material; validation of content by three groups of judges; and validation of appearance by the target audience. The validation with judges occurred with 45 specialists, of whom 22 were nurses in the surgical center, 22 anesthesiologists and three in the construction / evaluation area of educational materials. The content validity index was used in addition to the SAM form. In the second stage, the CRCT, there was a comparison between the control and intervention groups. The intervention was the use of the album, in a preoperative educational activity, developed in the maternity sector of a hospital in Juazeiro do Norte, Ceará, from June to August 2017. The sample of 90 pregnant women indicated for cesarean section under spinal anesthesia was randomly distributed in the control and intervention groups. A pre-test of the educational intervention was carried out. The expected outcome was the correct positioning of the pregnant women during spinal anesthesia, observed in the surgical center and evaluated according to the presence of the characteristics necessary for such position. The data were organized and tabulated using Microsoft Excel 2016 software, and analyzed by SPSS 20.0. Content validity index, concordance percentage analysis, and binomial test were used for content and appearance validation. For the analysis of data from the second stage of the research, descriptive and association analyzes were performed using the outcome variable, Chi-square test and likelihood ratio, with a confidence level of 95%. The study was approved by the committee of ethics in research at the Regional University of Cariri under opinion number 1,837,179. The results of the research were the construction of a serial album that converges with the guidelines of Safe Surgeries Saves Lives program and with the guidelines of the Stork Network. The mean overall S-CVI among the three groups was 0.95. From the SAM form, the album was judged as superior, obtaining a score of 91.42% among the nurses, 91.61% among the anesthesiologists and 96.21% among the technical judges. The target audience unanimously judged the material to be clear, easy to understand and relevant. Clinical 12 validation did not identify a statistically significant difference between the groups in relation to the outcome variable. However, statistical significance was identified between the following variables: number of lumbar puncture attempts and the anesthetist professional; the number of lumbar puncture attempts and the outcome variable; the outcome variable and the characteristics required for correct positioning (immobility, relaxed shoulders, lumbar spine flexion and cervical spine flexion). It is concluded that the serial album can be used by nurses who work in maternity and obstetric surgical centers as a tool to contribute to the adoption of correct and safe placement during cesarean section.